Reﬂections on Intergenerational Trauma: Healing as a Critical Intervention - Quinn, Ashley (First Peoples Child & Family Review, 2007)
The high numbers of Aboriginal children placed in provincial and territorial care demonstrates the need for effective interventions that directly address the legacy of trauma from colonialization. This paper argues that healing is a critical component of any intervention seeking to help Aboriginal Peoples and their children. Research on healing and recent government initiatives and legislation directed at preserving traditional Aboriginal healing practices are discussed. This article concludes with recommendations for various community members involved in the healing of Aboriginal Peoples.